فاعلية منهج تعليمي ترويحي بألعاب صغيرة في تطوير بعض القدرات الحركية وتعلم مهارتي التمرير والإرسال بالكرة الطائرة للتلاميذ بعمر ( 9-10 ) سنوات - إبراهيم، فراس سهيل (جامعة بابل - كلية التربية الرياضية, 2017)
The research objectives concentrated on preparing a recreational teaching program through using small games among students aged (9-10) years as well as identifying some motor abilities and learning the two skills scrolling and service in volleyball. The researcher used the experimental method to design two equal groups of the research sample, totaling (40) students out of the research community consisting of (130) students Safi Aldeen Alhili primary school in Babylon province .The research sample was divided into two groups experimental and control groups by 20 students . The researcher used tools and suitable devices to conduct special test in the research variables as well as implementing the syllabus of a recreational teaching program through using small games. The researcher also conducted a small exploratory experiment on a sample of the same school by 20 students .After conducting pre-tests and implementing the syllabus of a recreational teaching program for (8) weeks (2) units a week, totaling (16) teaching units. the time of each teaching unit is (40) minutes . After conducting post-tests and obtaining and processing data statistically ,the data were presented, analyzed and discussed depending on a related scientific references. The researcher has reached many conclusions. one of the most important that the researcher has reached that the recreational teaching program based on using small games play an important role in developing the motor abilities and learning skills of passing and service confronting from volleyball bottom . Based on the conclusions, the researcher recommended that it is necessary to use the recreational teaching program based on using the small games to develop other motor abilities and learning skills of volleyball.
تركزت أهداف البحث في إعداد منهج تعليمي ترويحي بألعاب صغيرة للتلاميذ بعمر (9-10) سنة فضلا عن ذلك التعرف على فاعلية هذا المنهج في تطوير بعض القدرات الحركية وتعلم مهارتي التمرير والإرسال بالكرة الطائرة للتلاميذ بعمر (9-10) سنة، واتبع الباحث المنهج التجريبي بتصميم المجموعتين المتكافئتين لعينة البحث البالغ عددها (40) تلميذاً من مجتمع البحث الأصلي البالغ (130) تلميذا يمثلون تلاميذ مدرسة صفي الدين الحلي الابتدائية للبنين في مركز محافظة بابل، وتم تقسيم عينة البحث إلى مجموعتين إحداها تجريبية والأخرى ضابطة وبواقع (20) تلميذاً، واستعمل الباحث الأدوات والأجهزة الملائمة لأجراء الاختبارات الخاصة بمتغيرات البحث، فضلا عن تنفيذ مفردات المنهج التعليمي الترويحي بألعاب صغيرة، وقام الباحث بإجراء تجربة استطلاعية مصغرة على عينة من تلاميذ المدرسة نفسها وبعدد (20) تلميذاً، وبعد إجراء الاختبارات القبلية وتنفيذ مفردات المنهج التعليمي الترويحي لمدة (8) أسابيع، وبعدد (2) وحدتين في الأسبوع، وبلغ المجموع الكلي (16) وحدة تعليمية، أما زمن الوحدة التعليمية فهو (40) دقيقة، وبعدها أجريت الاختبارات البعدية لمتغيرات البحث ، وبعد استخراج البيانات ومعالجتها إحصائيا تم عرضها وتحليلها ومناقشتها اعتمادا على المصادر العلمية ذات العلاقة، توصل الباحث إلى استنتاجات عدة من أهمها أدى المنهج التعليمي الترويحي القائم على استعمال الألعاب الصغيرة دوراً إيجابياً مهما في تطوير القدرات الحركية وتعلم مهارتي التمرير والإرسال المواجه من الأسفل بالكرة الطائرة، وفي ضوء هذه الاستنتاجات أوصى الباحث بضرورة استعمال المنهج التعليمي الترويحي القائم على استعمال الألعاب الصغيرة والمطبقة في البحث لتطوير قدرات حركية أخرى وتعلم مهارات الكرة الطائرة.
Keywords: القدرات الحركية; الألعاب الصغيرة; المنهج التعليمي الترويحي; الكرة الطائرة